The Effectiveness of Moringa Oleifera Seed Powder and Mixing Time (Fast-Low Speed) Using Jartest in Reducing Nitrate Levels in River Water - Jayadipraja, Erwin Azizi; Iqbah, Indra Purnama; Ardiansyah, Ririn Teguh; Bahtiar, La Ode; Hidayat, Muh Taufik; Asrullah, Muhammad; Alamsyah, Ryan; Rauf, Rahman (YCAB Publisher, 2024)
Background:Moringa oleiferais a fast-growing, long-lived plant that blooms throughout the year and can withstand extreme arid conditions. Objective:This study aims to examine the effectiveness of Moringa oleiferaseed powder in reducing nitrate levels in river water. Method:The research method employed in this study involved analysis using the Paired Sample Statistical Test. Result:The statistical test results revealed a significance value of 0.017 (p < 0.05) and a mixing time variation significance of 0.011 (p < 0.05). These values indicate that the null hypothesis (H0: there is no relationship between the independent and dependent variables) is rejected, while the alternative hypothesis (Ha: there is a relationship between the independent and dependent variables) is accepted. This implies a significant difference in the reduction of nitrate levels between the pretest and posttest data, demonstrating that the use of Moringaseed powder is effective in reducing nitrate levels. Conclusion:This study concludes that the administration of Moringaseed powder at a dose of 400 mg/L, with a mixing time of 2 minutes at a fast speed (80 rpm) and 20 minutes at a low speed (40 rpm), is most effective in significantly reducing nitrate levels in river water. Keywords:Moringa oleifera; nitrate levels; river water; Indonesia